2022
DOI: 10.1007/s10803-022-05450-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Worries of Individuals with Down Syndrome During the COVID-19 Pandemic: A Comparative Study in the UK

Abstract: The present study explored the effects of the pandemic on individuals with Down Syndrome (DS; n = 67) compared to other groups with Special Education Needs and Disabilities (SEND; n = 48) and their Typically Developing Siblings (TDS; n = 56). In total, 115 caregivers reported on their own anxiety and worries and of their children. Anxiety levels for individuals with DS appeared to be lower compared to other SEND populations and to TDS. In terms of worries, individuals with DS worried more about social-related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 68 publications
6
12
0
1
Order By: Relevance
“…While these experiences are not specific to parents of individuals with DS, families of children with special health care needs have significantly heightened risk of housing insecurity (Ghosh & Parish, 2015; Rose‐Jacobs et al, 2019) which can decrease mental and physical health of the parent (Guerrero et al, 2020; Suglia et al, 2011) and decrease the overall health (Ghosh & Parish, 2015; Rose‐Jacobs et al, 2019) and academic performance (Barling et al, 1999) of the child. Caregivers of individuals with DS report higher anxiety compared to caregivers of individuals with different disabilities and caregivers of typically‐developing individuals (Sideropoulos et al, 2023). Increased parental stress and anxiety has been shown to negatively affect parent/child relationships and child well‐being (Rose‐Jacobs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these experiences are not specific to parents of individuals with DS, families of children with special health care needs have significantly heightened risk of housing insecurity (Ghosh & Parish, 2015; Rose‐Jacobs et al, 2019) which can decrease mental and physical health of the parent (Guerrero et al, 2020; Suglia et al, 2011) and decrease the overall health (Ghosh & Parish, 2015; Rose‐Jacobs et al, 2019) and academic performance (Barling et al, 1999) of the child. Caregivers of individuals with DS report higher anxiety compared to caregivers of individuals with different disabilities and caregivers of typically‐developing individuals (Sideropoulos et al, 2023). Increased parental stress and anxiety has been shown to negatively affect parent/child relationships and child well‐being (Rose‐Jacobs et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Villani et al (2020) used a standardized assessment tool for 46 adults with DS in Italy and found that after the COVID‐19 lockdown, there was increased depression, worsened social withdrawal, and worsened ability to complete activities of daily living, but a decrease in aggressive behavior. A separate survey of 115 caregivers in the United Kingdom found lower anxiety levels for individuals with DS, more worry about friendships, and less worry about family‐related aspects compared to the other groups with other disabilities (autism spectrum disorder, unspecified intellectual disability, Williams syndrome, attention‐deficit hyperactivity disorder, and other unspecified syndromes or diagnoses) and their typically developing siblings (Sideropoulos et al, 2023). Given the potentially unique positive and negative impacts of the pandemic on individuals with DS, compared to individuals with other intellectual or physical disabilities, additional research is needed to evaluate the experience of COVID‐19 for these individuals and their families, especially within the United States as there is a relative paucity of such data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An international network of collaborators translated and disseminated the questionnaire in 16 languages, eventually reaching more than 10,000 families in 78 countries around the world. The questionnaire (original English version available in Supplementary Materials) and database have been used for other papers that have been published (Su et al, 2021;Furar et al, 2022;Sideropoulos et al, 2022aSideropoulos et al, , 2022b. One parent of each family completed the anonymous survey which contained a total of 299 questions.…”
Section: Methodsmentioning
confidence: 99%
“…The most challenging effects of the pandemic, especially during lockdowns, are depression, anxiety, and worries due to unemployment, losing loved ones, or being personally affected by the disease [3]. While there are several programs that psychologists and therapists carry out to enable recovery from these issues, there is an immense need to study worry using other sources [4]. Traditional methods of public health monitoring, like questionnaires and clinical tests, have certain limitations; for example, they only cover a 1 https://covid19.who.int limited number of participants and are restricted to the data collection period [5].…”
Section: Introductionmentioning
confidence: 99%